Outcome of Optical Internal Urethrotomy and Anastomotic Uretrhoplasty for Short Segment Bulbar Urethral Stricture - Jahan, Mohammad Sarwar; Alam, Md Shawkat; Alam, Md Naushad; Hasan, Shahriar Md Kabir; Kamal, Md Mostofa; Chowdhury, Anup Roy; Dey, Debashis (Bangladesh Journal of Urology, 2020)
Background: Urethral stricture diseases are common urological problems in our country. The etiologies include iatrogenic, trauma, infection, congenital and very few are idiopathic. Urethral strictures have the potential for great negative impact on patients. These have several treatment modalities, ranging from simple dilations to complex multistaged urethroplasties. Optical internal urethrotomy and anastomotic urethroplasty are the common procedures among them which are particular topics in this study. Objectives: To evaluate the outcome of two surgical techniques- Optical Internal Urethrotomy (OIU) and Anastomotic Urethroplasty. Methodology: A total of 50 patients with short segment bulbar urethral strictures were consecutively included in the study. Purposive sampling method was applied. The present outcome clinical study was conducted in the department of Urology, National Institute of Kidney Diseases and Urology, Sher-E-Bangla Nagar, Dhaka, Bangladesh over a period of 1 year from February 2016 to January 2017. Student’s t-test and chi-square test were applied for hypothesis testing. ‘P’ value <0.05 was considered as significant. Result: There is no significant difference between two groups regarding age, history of previous operation for stricture urethra, mode of clinical presentations before intervention, immediate post-operative complication and uroflowmetry during follow-up. But length of stricture of two groups, urinary stream at 3 and 6 months after operation, urinary tract infection at 6 month after operation, recurrence of stricture in two groups were statistically significant (p<0.05). Conclusion: The study concluded that anastomotic urethroplasty was an effective and satisfactory technique for the treatment of short segment bulbar urethral stricture. The morbidity and complications were low and outcomes were excellent. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.30-35